z=(x-y)F(x2+y2) obtain the partial differential equation by eliminating the arbiyrary function from the following equation
Let us obtain the partial differential equation by eliminating the arbiyrary function from the following equation "z=(x-y)F(x^2+y^2)." Since "z_x'=F(x^2+y^2)+(x-y)F'(x^2+y^2)2x" and "z_y'=-F(x^2+y^2)+(x-y)F'(x^2+y^2)2y," we conclude that "yz_x'=yF(x^2+y^2)+2xy(x-y)F'(x^2+y^2)" and "xz_y'=-xF(x^2+y^2)+2xy(x-y)F'(x^2+y^2)." After substracting we get the equation "yz_x'-xz_y'=yF(x^2+y^2)+xF(x^2+y^2)." Then "yz_x'-xz_y'=(x+y)F(x^2+y^2)," and hence "F(x^2+y^2)=\\frac{yz_x'-xz_y'}{x+y}." It follows that "z=(x-y)F(x^2+y^2)=(x-y)\\frac{yz_x'-xz_y'}{x+y}." Consequently, the partial differential equation is the following:
"z(x+y)=(x-y)(yz_x'-xz_y')."
Comments
Leave a comment